A General Practice Audit Comparing the Rate of Pneumococcal Vaccine Uptake Among Patients with Diabetes Mellitus, Before and After Intervention - Corrigan, Ciara; Sloan, Samual; Rushe, Paul (Trinity Student Medical Journal, 2020)
The pneumococcal polysaccharide vaccine was introduced for at-risk groups in Ireland in 1996 and it has been demonstrated that increased vaccination rates result in fewer hospital visits in at-risk groups. An audit was carried out from October 2017 until January 2018 in a rural general practice catering for just over 2,000 patients. It was hypothesised that, from direct observation, there was a lack of uptake of the pneumococcal vaccine in certain at-risk patient groups, such as patients with diabetes mellitus. The findings from this were used to guide intervention aimed at encouraging uptake of the pneumococcal vaccine. Data was collected to include the vaccination status of all patients with diabetes mellitus in the practice. The results showed 89 patients (59.3%) had never received the vaccine. In addition, a further 23 (15.3%) patients were due a booster. From the re-audit, following intervention to encourage uptake, which included direct advice and encouragement from the practice doctors and nurses, in addition to a text message reminder sent to patients, 22 patients attended for vaccination, giving an uptake rate of 19.6%. The ideal scenario is for all patients with diabetes mellitus to be vaccinated which would amount to improved quality of life for patients. Whilst a target of 100% is difficult to achieve, the expectation would be to have the majority of patients vaccinated according to current guidelines. In addition, the practice would ensure compliance with those guidelines and recommendations regarding vaccination and would also generate revenue, which is important in order to maintain a viable business model within general practice.